2016
DOI: 10.1093/jb/mvw067
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of ratacss3and characterization of mammalian propionyl-CoA synthetase in the liver mitochondrial matrix

Abstract: Among the three acyl-CoA synthetase short-chain family members (ACSS), ACSS3 is poorly characterized. To characterize ACSS3, we performed molecular cloning and protein expression of rat acss3 and determined its intracellular localization, tissue distribution, and substrate specificity. Transient expression of rat ACSS3 in HeLa cells resulted in a 10-fold increase of acetyl-CoA synthetase activity compared with that in control cells. The acss3 transcripts are expressed in a wide range of tissues, with the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…Previous work has also showed that chronic intragastric acetate infusion in rats promotes postprandial hyperinsulinaemia and increases liver triglyceride content . The conversion of SCFAs into metabolic intermediates is initially determined by the acyl‐CoA synthetase short‐chain family members (ACSS) . Human hepatocytes express the cytosolic isoform ACSS2 , which has high specificity for acetate and increases the availability of acetyl‐CoA for lipid synthesis .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work has also showed that chronic intragastric acetate infusion in rats promotes postprandial hyperinsulinaemia and increases liver triglyceride content . The conversion of SCFAs into metabolic intermediates is initially determined by the acyl‐CoA synthetase short‐chain family members (ACSS) . Human hepatocytes express the cytosolic isoform ACSS2 , which has high specificity for acetate and increases the availability of acetyl‐CoA for lipid synthesis .…”
Section: Resultsmentioning
confidence: 99%
“…The conversion of SCFAs into metabolic intermediates is initially determined by the acyl‐CoA synthetase short‐chain family members (ACSS) . Human hepatocytes express the cytosolic isoform ACSS2 , which has high specificity for acetate and increases the availability of acetyl‐CoA for lipid synthesis . Evidence highlights that, together with higher insulin levels, humans with NAFLD have an elevated expression of hepatic genes that favour fat accumulation, with increased expression of acetyl‐CoA carboxylase (ACC) and fatty acid synthase (FASN), which are key enzymes in hepatic DNL .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The enzymes involved in converting free acetate to acetyl-CoA are known as ACSS and three forms are currently known (family members 1–3) (Yoshimura et al, 2017). These enzymes expend ATP to generate acetyl-CoA from acetate and coenzyme A. ACSS1 and ACSS3 are mitochondrial matrix enzymes involved in the oxidation of acetate and propionate respectively for energy derivation, whereas Acss2 is a nuclear-cytoplasmic enzyme involved in lipid synthesis and protein acetylation reactions.…”
Section: Discussionmentioning
confidence: 99%